Rare presentation of mycoplasma pneumonia: a case report - Vaishnavi, Bhimana; Janakiraman, Lalitha; Dhanalakshmi, K. (International Journal of Contemporary Pediatrics, 2020)
Mycoplasma is a frequent cause of community acquired pneumonia in children accounting for 20 percent of the cases. Though CNS complications are the most common extra pulmonary manifestations of M. pneumoniae stroke is a rare entity. Here we report a case of 7 years old male child with macrolide resistant M. pneumoniae complicated pneumonia that developed right hemiparesis and dysphasia. Brain magnetic resonance imaging and angiography showed left fronto parietal infarct and left carotid artery stenosis. He responed to non-macrolide antimicrobial regimen. This potential yet rare complication should be considered and closely monitored for in children presenting with complicated pneumonia.